Nanostructured GelMA colloidal gels as bioinks for freeform multi-mode 3D printing: better replacement for the classical GelMA polymeric inks - Qifan Wang; Kaiwen Chen; Yonggang Zhang; Fei Shao; Xiangyuan Tan; Qiwei Ying; Libin Wang; Changle Ren; Lijun Zhang; Huanan Wang (Bioactive Materials)
Methacrylated gelatin (GelMA) hydrogels have been well-recognized as a widely-used natural polymer for biofabrications due to the adaptability for multiple crosslinking schemes, desirable biocompatibility and biodegradability, and ease of chemical functionalization. With regard to 3D bioprinting, however, GelMA has shown unsatisfactory printing stability and accuracy due to slow sol-gel transition, suboptimal mechanical strength, and strict temperature control for printing. We herein developed an innovative dual-crosslinkable colloidal inks composed of self-assembled GelMA nanospheres with 80 % self-healing efficiency, which outperform the traditional GelMA polymeric inks in terms of enhanced printability and fidelity, broader printing temperature range, adjustable mechanical strength ranging from brain analogue 2.83 kPa to cardiac analogue 52.45 kPa, and improved bio-functionalities evidenced by the elevated hydrophilicity, mass transfer efficiency and prolonged drug release profile. Moreover, the granulation design of GelMA inks unlocked freeform 3D printing modes such as direct multi-ink writing, embedded printing, but also allowed in-situ printing directly at the bleeding wound sites due to the outstanding hemostatic efficacy and network stability of colloidal gels. In general, our nanostructured GelMA colloidal inks present a better replacement for the traditional GelMA polymeric inks in 3D bioprinting, which establishes a foundation for bench-to-bedside translations of 3D printing techniques towards more practical clinical applications.